2021
DOI: 10.1021/acs.macromol.1c00349
|View full text |Cite
|
Sign up to set email alerts
|

PEG-Based Methacrylate Tetrablock Terpolymers: How Does the Architecture Control the Gelation?

Abstract: An ABCA tetrablock terpolymer with excellent thermogelling properties in aqueous solutions has been identified by tuning the architecture of ethylene glycol-based tetrablock terpolymers. Specifically, it gels at concentrations as low as 5 wt % at a wide range of temperatures, including body temperature. Nine tetrablock copolymers based on hydrophilic oligo­(ethylene glycol) methyl ether methacrylate with average molar mass (MM) 300 g mol–1 (OEGMA300, A), hydrophobic n-butyl methacrylate (BuMA, B), and hydrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 128 publications
2
11
0
Order By: Relevance
“…As shown in Table 1, the theoretical molar mass and composition was compared to the number average molar mass (M n ) given by GPC, and the composition given by NMR. From the GPC results, we found that the dispersity (Đ) of all the final products were smaller than 1.21, similar to previous reported studies on OEGMA based polymers, 26,[90][91][92][93] indicating a successful synthesis of well-defined polymers. The M n s of the final products were between 9400 g mol −1 and 11 800 g mol −1 , higher than the theoretical molar mass (8100 g mol −1 ).…”
Section: Molar Mass Characterisationsupporting
confidence: 88%
See 1 more Smart Citation
“…As shown in Table 1, the theoretical molar mass and composition was compared to the number average molar mass (M n ) given by GPC, and the composition given by NMR. From the GPC results, we found that the dispersity (Đ) of all the final products were smaller than 1.21, similar to previous reported studies on OEGMA based polymers, 26,[90][91][92][93] indicating a successful synthesis of well-defined polymers. The M n s of the final products were between 9400 g mol −1 and 11 800 g mol −1 , higher than the theoretical molar mass (8100 g mol −1 ).…”
Section: Molar Mass Characterisationsupporting
confidence: 88%
“…The cloud points of the 1% w/w polymer solutions with various solvents given by the UV-VIS are listed in Table 2. The cloud point of a polymer can be influenced by the molar mass, 26 composition, 32,94–97 structure, 98–101 architecture, 62,91,102 and solvent. 103,104…”
Section: Resultsmentioning
confidence: 99%
“…This is observed at high contents in P1, as the concentrated solutions (15 and 20 w/w%) of the triblock terpolymer in PBS only present gel syneresis upon temperature increase, with no precipitation being detected, i.e., the gel does not progressively exclude more solvent. This double crossover has been previously observed by our group on OEGMA300 x -b-BuMA y -b-DEGMA z -b-OEGMA300 x tetrablock terpolymer [58]. The MM of the OEGMA300 x homopolymers plays a critical role in the stability of the gels, as the higher the MM, the higher the maximum storage modulus of the gels (Figure 4 from black (OEGMA300 10 ) to red/green (OEGMA300 31 /OEGMA300 47 ) to blue (OEGMA300 75 )).…”
Section: Homopolymers As Additives In Thermogelling Triblock Copolymer Solutions-rheological Propertiessupporting
confidence: 78%
“…Our group has recently reported a novel combination of methacrylate repeated units, which produces thermoresponsive polymers with a sharp sol-gel transition [56][57][58]. More specifically, the polymers consist of (i) the hydrophilic oligo (ethylene glycol) methyl ether methacrylate with average MM 300 g mol −1 (OEGMA300, A unit), which is also thermoresponsive at approximately 70 • C, depending on the MM [59], (ii) the hydrophobic n-butyl methacrylate (BuMA, B unit), and (iii) the hydrophilic and thermoresponsive (CP approximately 30 • C) [59] di(ethylene glycol) methyl ether methacrylate (DEGMA, C unit).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation